Electrophoretic properties of the scrapie agent in agarose gels. - Prusiner, S B (1980)
The molecular properties of the scrapie agent were investigated by subjecting partially purified preparations to electrophoresis on agarose gels. When electrophoresis was performed at room temperature in the presence of sodium dodecyl sulfate (NaDodSO4), most of the recoverable agent was found at the top of the gel, consistent with previous studies indicating aggregation of the agent upon exposure to elevated temperatures. In addition, less than 5% of the agent applied to the gel was found after electrophoresis, even though the study was performed with a low concentration of NaDodSO4 (0.1%). Further studies on the inactivation of the agent by NaDodSO4 suggest that this may be, in part, a function of the NaDodSO4: protein ratio in the sample. In contrast, sodium N-lauroyl sarcosinate (Sarkosyl) did not inactivate the agent in concentrations as high as 5% (wt/vol). Virtually all of the infectivity could be recovered after electrophoresis of the agent into 0.6% agarose gels at 4 degrees C in the presence of 0.2% Sarkosyl. Digestion of the preparations with micrococcal nuclease and proteinase K prior to Sarkosyl electrophoresis caused a substantial portion of the agent to migrate ahead of DNA fragments of 1 x 10(6) daltons. The behavior of the scrapie agent in electrophoretic gels is consistent with earlier studies showing that the monomeric form of the agent has a sedimentation coefficient of less than or equal to 40 S. Thus, the smallest or monomeric form of the agent is smaller than any known animal virus.